2000
DOI: 10.4049/jimmunol.164.6.3222
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase and c-Jun-NH2-Terminal Kinase Regulate RANTES Production by Influenza Virus-Infected Human Bronchial Epithelial Cells

Abstract: Airway epithelial cells which are the initial site of influenza virus (IV) infection are suggested to participate in airway inflammatory response by expressing various cytokines including RANTES; however, the intracellular signal that regulates RANTES expression has not been determined. In the present study, we examined the role of p38 mitogen-activated protein (MAP) kinase, extracellular signal-regulated kinase (Erk), and c-Jun-NH2-terminal kinase (JNK) in RANTES production by IV-infected human bronchial epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 51 publications
(45 reference statements)
8
142
1
Order By: Relevance
“…Previous reports have shown that p38 kinase regulates influenza virus-induced RANTES expression in bronchial epithelial cells (39) and is involved in TNF-␣ production during H5N1 infection (18). Therefore, we explored the effect of IRF3 knockdown and p38 kinase inhibitor treatment both singly and in combination on H5N1-induced cytokine and chemokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that p38 kinase regulates influenza virus-induced RANTES expression in bronchial epithelial cells (39) and is involved in TNF-␣ production during H5N1 infection (18). Therefore, we explored the effect of IRF3 knockdown and p38 kinase inhibitor treatment both singly and in combination on H5N1-induced cytokine and chemokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that p38 MAPK and JNK, but not ERK1/2, regulate RANTES expression in influenza virus-infected bronchial epithelial cells. Moreover, MAPK/ERK kinase-specific inhibitors have been reported to inhibit the nuclear export of viral ribonucleoprotein complexes and impair the activity of nuclear-export protein, NEP/NS2, in the virus replication cycle [20]. The zinc finger is a novel motif found in Zinc finger proteins which bind to DNA.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with Andrea L. Kroeker's study [19] who reported that the down regulated proteins generally belong to cell adhesion and lipid metabolism. The proteins from pandemic influenza A/H1N1/2009 are MAPK7, Zinc finger proteins, Pyruvate dehydrogenase kinases and Beta-defensin 108B are mostly involved in anti-viral mechanism [10,20,28] and also help in host defense system. The proteins from influenza type B majorly IFIT2 along with Interleukin-1 receptor-associated kinase (IRAK) plays a central role in cell signaling processes as cited earlier [9,18].…”
Section: Resultsmentioning
confidence: 99%
“…RANTES representing by its chemotactic activity for eosinophils plays a pivotal role in the induction of airway inflammation of asthmatics through the recruitment of eosinophils to the inflammation site of airway after influenza virus infection [38] . Whether RANTES secretion induced by dengue virus infection of liver cells can recruit immune cells deserves further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, HIV infection can activate RANTES through phosphorylation of Erk [37] . And Influenza virus infection can up-regulate RANTES expression through p38 and JNK [38] . Dengue virus can induce DNA binding activity of NF-IL-6 and up-regulates RANTES expression [9] .…”
Section: Introductionmentioning
confidence: 99%